A genome‐wide significant association on chromosome 15 for congenital entropion in Swiss White Alpine sheep. (16th January 2020) - Hirter, N.; Letko, A.; Häfliger, I. M.; Becker, D.; Greber, D.; Drögemüller, C.
Summary: Entropion is a known congenital disorder in sheep presumed to be heritable but no causative genetic variant has been reported. Affected lambs show a variable inward rolling of the lower eyelids leading to blindness in severe cases. In Switzerland, the Swiss White Alpine (SWA) breed showed a significantly higher prevalence for entropion than other breeds. A GWAS using 150 SWA sheep (90 affected lambs and 60 controls), based on 600k SNP data, revealed a genome‐wide significant signal on chromosome 15. The 0.2 Mb associated region contains functional candidate genes, SMTNL1 and CTNND1 . Pathogenic variants in human CTNND1 cause blepharocheilodontic syndrome 2, a rare disorder including eyelid anomalies, and SMTNL1 regulates contraction and relaxation of skeletal and smooth muscle. WGS of a single entropion‐affected lamb revealed two private missense variants in SMTNL1 and CTNND1 . Subsequent genotyping of both variants in 231 phenotyped SWA sheep was performed. The SMTNL1 variant p.(Asp452Asn) affects an evolutionary conserved residue within an important domain and represents a rare allele, which occurred also in controls. The p.(Glu943Lys) variant in CTNND1 represents a common variant unlikely to cause entropion as the mutant allele occurred more frequently in non‐affected sheep. Therefore, we propose that these protein‐changing variants are unlikely to explain the phenotype. Additionally, WGS of three further disconcordant pairs of full siblings was carried out but revealed no obvious causative variant. Finally, we conclude that entropion represents a more complex disease caused by different non‐coding regulatory variants.